The effects of water addition and baking time on process optimization of pumpkin muffins: a pilot plant scale study - Rina Rismaya; Elvira Syamsir; Budi Nurtama; Nawawee Tohyeng (Hasanuddin University Food Science and Technology Study Program, 2022)
Pumpkin muffins are rich in fiber but have low expansion volume and high hardness. To date, research on pumpkin muffins has only been conducted on a laboratory scale. Therefore, a pilot plant study is needed to optimize its production on an industrial scale. This work aimed to determine the processing conditions that could produce the optimum quality of pumpkin muffins on a pilot plant scale. Water addition and baking time were chosen as optimization variables, color, moisture content, expansion volume and hardness were selected as response variables. Optimization was conducted using Response Surface Methodology in Design Expert 7.0® program. The mathematical models for brightness and hue were cubic models, and those for moisture content, expansion volume, and hardness were quadratic models. Optimization results with a desirability value of 0.884 were obtained from the addition of 48% water and baking time of 22 minutes. The resulting pumpkin muffins had lightness of 41.21, hue of 70.74, moisture content of 27.96%, expansion volume of 185.39%, and hardness of 2.91 N and contained 27.96% moisture, 2.23% ash, 18.59% fat, 5.85% protein, 45.37% carbohydrates, and 8.76% dietary fiber. These findings provide new insights for researchers and bakery industries to improve the quality of muffins from local food sources.